Вскрытие покажет: [роман] / Владимир Николаев - Николаев Владимир Николаевич (Черная кошка, 1998)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 35804 / Цена: 25.00 / Сис.шифр: Р2 / Авт.знак: Н 63 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6